2007
DOI: 10.1111/j.1468-1331.2006.01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cerebral blood flow velocity in apolipoprotein E ɛ4 allele carriers with mild cognitive impairment

Abstract: The aim of this study was to investigate the changes in cerebral blood flow velocity (CBFV) and its relation to apolipoprotein E (apoE) epsilon4 allele in mild cognitive impairment (MCI). Thirty MCI and 30 controls were assessed using Mini-Mental State Examination (MMSE) and Cambridge Cognitive Examination-Chinese version (CAMCOG-C), and then insonated in the anterior (ACA), middle (MCA) and basilar (BA) cerebral arteries using transcranial Doppler ultrasonography. Compared with controls, MCI showed significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Another measure showing predictive value in AD is CBF velocity (CBFv), which may distinguish between normal controls, individuals at genetic risk, adults with MCI, and AD patients (Maalikjy Akkawi et al 2003; Maalikjy Akkawi et al 2005; Sun et al 2007; Claassen et al 2009). Similarly, research looking at flow territory asymmetry, using vessel encoding ASL (VE-ASL), suggests that it is a promising predictor of cognitive decline, and should be the focus of further investigation (Donahue et al 2014).…”
Section: Future Directions and Emerging Biomarkersmentioning
confidence: 99%
“…Another measure showing predictive value in AD is CBF velocity (CBFv), which may distinguish between normal controls, individuals at genetic risk, adults with MCI, and AD patients (Maalikjy Akkawi et al 2003; Maalikjy Akkawi et al 2005; Sun et al 2007; Claassen et al 2009). Similarly, research looking at flow territory asymmetry, using vessel encoding ASL (VE-ASL), suggests that it is a promising predictor of cognitive decline, and should be the focus of further investigation (Donahue et al 2014).…”
Section: Future Directions and Emerging Biomarkersmentioning
confidence: 99%
“…Previous studies have demonstrated associations between decreased MFV and older age [37] , mild cognitive impairment [38] , Alzheimer or vascular dementia [39] . In our study, higher MFV is associated with normal SPECT perfusion, fewer WMA, higher MoCA scores and older age.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, people suffering from MCI were shown to have a significantly decreased blood flow in the middle and anterior cerebral artery when compared to controls [6]. Moreover, the Rotterdam Study demonstrated that cerebral hypoperfusion precedes and possibly contributes to the onset of clinical dementia [4].…”
Section: Relationship Between Endothelial Vasodilator Function Andmentioning
confidence: 99%
“…With increasing life expectancy, dementia is a global public health problem with no cure or effective medical treatment currently available [1]. A growing body of evidence suggests that the initiation and progression of dementia is a consequence of poor cerebral vascular function and hypoperfusion [2,3,4,5,6]. The maintenance of cerebral blood flow (CBF) is crucial for normal brain functioning.…”
Section: Introductionmentioning
confidence: 99%